Finite Element Analysis of Shock Absorption of Porous Soles Established by Grasshopper and UG Secondary Development. (19th November 2020) - Liu, Xiaoying; Yue, Yong; Wu, Xuyang; Hao, Yanhua; Lu, Yong
Abstract : On the basis of computer aided modeling technology, this paper proposes a porous structure modeling method based on Grasshopper visual programming language and Unigraphics NX (UG) secondary development platform. The finite element model of the foot was established, and then models of shoe soles with four basic porous structures of cross, diamond, star, and x were established. Each structure was set with a cylindrical radius of 1, 2, and 3 mm, and a total of 12 porous structure sole models were established. The shock absorption effect of the sole on the foot was evaluated by the deformation of the sole, the peak plantar pressure, and the peak stress of metatarsal bones. It is found that the maximum value of the sole deformation of the diamond porous sole is 4.725 mm, the peak plantar pressure is 105.1 Pa, and the first and second metatarsal peak pressures are 2.230 MPa and 3.407 MPa, which have the best shock absorption effect. It shows that the porous structure plays an important role in the cushioning of the sole. The biomechanical effects of porous soles on feet are studied by computer-aided technology and finite element analysis. This study provides a new research method for the cushioning design of shoe soles and has important reference value for the design of footwear.